2017
DOI: 10.1002/fuce.201600183
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low Mass Sputtered and Conventional Catalyst Layers on Plasma‐etched Nafion for PEMFC Applications

Abstract: This paper presents performance results for the use of plasma‐etched Nafion membranes to suppress polarization losses in proton exchange membrane fuel cells (PEMFCs) configured from 0.1 mg cm−2 conventional Pt/C dispersion and 0.02 mg cm−2 ultra‐thin sputter‐deposited Pt catalyst layers. Four MEA configurations, namely, etched membrane‐conventional electrode, pristine membrane‐conventional electrode, etched membrane‐sputter electrode, and pristine membrane‐sputter electrode cells were explored, and their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Nonetheless, the surface of E-N212 with a thickness of ∼25 μm was irregular and rugged, as seen in Figure b, which indicated that plasma treatment not only decreased membrane thickness but also modified the surface topography. Specifically, we observed that the root-mean-square (RMS) factor, which reflects the extent of surface roughness, increased dramatically from 1.61 to 331 nm and this is consistent with the previous plasma etching studies. ,, To investigate the surface morphology change depending on the annealing temperature, we have varied annealing temperatures. It has been reported that the Nafion membrane has two kinds of glass transition temperatures ( T g ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, the surface of E-N212 with a thickness of ∼25 μm was irregular and rugged, as seen in Figure b, which indicated that plasma treatment not only decreased membrane thickness but also modified the surface topography. Specifically, we observed that the root-mean-square (RMS) factor, which reflects the extent of surface roughness, increased dramatically from 1.61 to 331 nm and this is consistent with the previous plasma etching studies. ,, To investigate the surface morphology change depending on the annealing temperature, we have varied annealing temperatures. It has been reported that the Nafion membrane has two kinds of glass transition temperatures ( T g ).…”
Section: Resultssupporting
confidence: 88%
“…Specifically, we observed that the root-mean-square (RMS) factor, which reflects the extent of surface roughness, increased dramatically from 1.61 to 331 nm and this is consistent with the previous plasma etching studies. [14][15][16]27,28 To investigate the surface morphology change depending on the annealing temperature, we have varied annealing temperatures. It has been reported that the Nafion membrane has two kinds of glass transition temperatures (T g ).…”
Section: Mechanical Properties Of E-t-n212 and E-t-n211mentioning
confidence: 99%
See 1 more Smart Citation
“…However, both of these processes are based on the two-dimensional flat membranes. In recent years, many new and improved technologies have tried to replace the commonly used flat membrane but forming various patterns on the membrane started to be considered from a three-dimensional perspective with the interface characteristics of PEM|CL [75][76][77][78][79][80].…”
Section: Interface Of Pem|clmentioning
confidence: 99%
“…Proton conduction is one of the common natural processes and very important in life activities, such as proton translocation by the adenosine triphosphate synthase complex and the proton transfer in biochemical processes. It is well-known that protons can be conducted laterally along the membranes or by specific amino acids such as the proton pump activity of bacteriorhodopsin protein. Beyond biochemical systems, proton conduction also plays an important role in electrochemical devices, like sensors, batteries, and fuel cells for instance. Solid proton exchange membranes (PEMs) are commonly used in these devices, where protons are transported through the membranes. , Therefore, PEMs need to possess high proton conductivity, selectivity, and mechanical stability. Perfluorinated ionomers, especially Nafion, are widely used as PEM materials for fuel cells. Nafion is composed of a hydrophobic tetrafluoroethylene-like backbone and side chains terminated with hydrophilic sulfonic groups . Strongly acidic sulfonic groups, when hydrated, combine with water molecules and ionize, so that proton conduction channels form with connected sulfonic ionic clusters ((−SO 3– ) n ).…”
Section: Introductionmentioning
confidence: 99%